Treinamento muscular respiratório em crianças sedentárias - Pereira, Thaís Yolanda (2013)
Introduction: As far as athletes exercise the muscles with loads above the usual levels in order to increase the resistance and tolerance, individuals with ventilatory muscles function decreased can achieve a similar training effect through the use of a device that provides a resistive load to the respiratory muscles. The respiratory muscles react to the resistive training such as other organism muscles. The principles involved in increasing tolerance and resistance to usual exercise and training programs with loads are, consequently, the same involved in the respiratory muscle training. Objectives: To prove the efficacy of a respiratory muscle training in sedentary children with respiratory muscle weakness. Method: In a previous study, we evaluated the maximum respiratory pressures of sedentary children and we identified respiratory muscles weakness. Thereafter, we proposed to these children a respiratory muscles training program. The children were treated with the THRESHOLD IMT® respiratory muscle trainer and exercises of strengthening for abdominals during eight weeks, twice a week. Results: In the pre-intervention assessment, the average presented by the population was -53,00 ± 13,746 for maximum inspiratory pressure (MIP) and 44,50 ± 11,697 for maximum expiratory pressure (MEP). In the post-treatment assessment, the average presented was -87,67 ± 12,847 for MIP and 79,33 ± 9,890 for MEP, what indicates that there was an increase in the respiratory muscles’ strength. Conclusion: The respiratory muscle training with the THRESHOLD IMT® and the abdominals strengthening exercises are effective tools in the treatment of sedentary children with respiratory muscles weakness